A Proposed Artificial Intelligence-Based System for Developing E-management Skills in Saudi Primary Schools - Hagag, Ahlam Mahmoud; Elnaggar, Mohamed Elsayed; Sharaf, Rasha Saad (European Scientific Journal, ESJ, 2023)
This study aims to investigate the impact of Artificial intelligence-driven solutions on school leaders’ proficiencies. Leaders have the responsibility of making decisions in educational institutions as well as carrying out routine tasks daily. Artificial intelligence-assisted applications have noteworthy contributions to the field of educational management. The scope of this study is limited to selected features; data analytics, chatbot, and e-survey. The basic design of this study started with analyzing literature in this domain. This was followed by designing a system consisting of four models: building a dashboard, predicting students’ results, creating a chatbot for responding to parents’ queries, and creating an e-survey for measuring staff satisfaction. The prominent finding of this study is the significant impact of Artificial intelligence on leaders’ competencies.